Establishment of a new line of plasmodium knowlesi / Amirah Amir - Amirah, Amir (2016)
Plasmodium knowlesi has been used as an important malaria research tool for many years and is now recognized as an important cause of human malaria in parts of Southeast Asia. The strains of P. knowlesi currently used for basic and applied research were isolated over half a century ago, raising concerns that they are no longer representative of present-day parasite population. In this study, a new line of P. knowlesi (UM01 line) from a human malaria patient was isolated, expanded, characterized, and compared with a standard reference strain of P. knowlesi (A1-H.1 line). The UM01 and A1-H.1 lines readily invade both human and macaque (Macaca fascicularis) normocytes with a preference for younger red cells that reached significance for the A1-H.1 with human reticulocytes. Interestingly, while the invasion of P. knowlesi (UM01 and A1-H.1 lines) into human cells is strictly dependent on the presence of the Duffy antigen/receptor for chemokines (DARC), this dependence on Duffy is highly variable for the invasion of monkey red cells. Despite the above similarities between these two lines, there are a number of key differences including the invasion efficiency, length of asexual cycle and the ability to produce gametocytes. The UM01 line infected red blood cells shows a reduction in overall cell deformability especially in schizont infected human red blood cells as well as ring, trophozoite and schizont infected monkey red blood cells. Additionally, Anopheles cracens, the Peninsular Malaysia mosquito vector of P. knowlesi was colonized. Although the colonization was successful, attempts to infect them with P. knowlesi (UM01 line) was not. With reports of human knowlesi infection increasing in regions where cases of other human malaria parasites have been brought down, reliance on limited number of P. knowlesi strains that have been passaged through hundreds of monkeys over the last 50 to 80 years significantly limits our understanding of the current parasite population. Therefore, isolation of a new and locally obtained P. knowlesi strain cannot be overemphasized.